Method for using polyester shrink film to adherend
Patent Information
- Application Number
- JP2024194063
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-03-28
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2044-01-31
AI Technical Summary
【0015】 又、本発明の更に別の態様によれば、全体量(100重量%)に対して、30~80重量%の非晶性ポリエステル樹脂と、20~70重量%の結晶性ポリエステル樹脂(但し、78℃のガラス転移温度を有する低結晶性ポリエステル樹脂及び結晶性ポリエステル樹脂を除く。)と、を含むポリエステル系樹脂組成物に由来したポリエステル系シュリンクフィルムの被着体に対する使用方法であって、 非晶性ポリエステル樹脂は、反応成分の全体量(100重量部)につき、おいて、テレフタル酸を100重量部に対して、エチレングリコールを50~80重量部と、ジエチレングリコールを5~20重量部と、1,4-シクロヘキサンジメタノール又はネオペンチルグリコールを20~50重量部、とからなり、 結晶性ポリエステル樹脂は、反応成分の全体量(100重量部)につき、テレフタル酸を90重量部以上、エチレングリコールを90重量部以上、とからなり、 下記構成(a´´)~(c´´)を満足することを特徴とするポリエステル系シュリンクフィルムの被着体に対する使用方法である。 構成(a´´):JIS K 7244-4に準拠し、動的粘弾性測定装置を用いて得られる損失弾性率曲線において、70℃以上、95℃以下の温度域に、第1の損失弾性ピークを有する。 構成(b´´):JIS K 7244-4に準拠し、動的粘弾性測定装置を用いて得られる損失弾性率曲線において、110℃以上、140℃以下の温度域に、第1の損失弾性ピークと逆方向に凸状である第2の損失弾性ピークを有する。 構成(c´´):80℃の温水に10秒間浸漬したときの、主収縮方向における熱収縮率が30%以上である。 すなわち、所定配合組成に由来したポリエステル系シュリンクフィルムの被着体に対する使用方法につき、動的粘弾性測定装置(DMA)を用いて得られる損失弾性率曲線において、異なる温度域に、それぞれ第1の損失弾性ピークと、第2の損失弾性ピークを有することによって、ガラス領域と、ゴム弾性領域とのバランスが良くなって、所定温度における熱収縮率を、精度良く制御し、ひいては、耐シワ特性を向上させることができる。
Smart Images

Figure 2025024001000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for using a polyester shrink film on an adherend. More specifically, the present invention relates to a method for using a polyester-based shrink film having excellent wrinkle resistance, in which the loss factor peak, etc. measured using a dynamic viscoelasticity measuring device (hereinafter sometimes referred to as DMA) is controlled over multiple temperature ranges, on an adherend. [Background technology]
[0002] Conventionally, shrink films have been widely used as base films for labels on PET bottles, etc. In particular, polyester resins are widely used due to their excellent transparency and strength. These shrink films are thermally shrunk by passing through a tunnel that generates hot air or steam, and then attached to the container, but shrinkage differences (unevenness) may occur during thermal shrinkage, resulting in wrinkles and uneven coloring. In view of this, various heat-shrinkable polyester films have been proposed to prevent wrinkles and color unevenness caused by shrinkage differences (unevenness) that occur during heat shrinkage.
[0003] For example, a heat-shrinkable polyester film has been proposed that has a high heat shrinkage rate in the width direction and a small heat shrinkage rate in the longitudinal direction, has high mechanical strength in the longitudinal direction, has good perforation opening properties, and has excellent shrink finish properties (see Patent Document 1). More specifically, it is a biaxially stretched heat-shrinkable polyester film that satisfies the following requirements (1) to (5). (1) 1,4-cyclohexanedimethanol is used as an amorphous monomer in an amount of 5 mol % to 30 mol % based on 100 mol % of the alcohol component, (2) When the film is immersed in 98°C hot water for 10 seconds, the hot water heat shrinkage rate is 60% or more and 90% or less in the main shrinkage direction of the film. (3) When the film is immersed in 98°C hot water for 10 seconds, the hot water heat shrinkage rate is between -5% and 5% in the direction perpendicular to the main shrinkage direction of the film. (4) The right-angle tear strength per unit thickness in the direction perpendicular to the main shrinkage direction after shrinking 10% in the main shrinkage direction in 80°C hot water is 180 N / mm or more and 350 N / mm or less. (5) The maximum shrinkage stress in the main shrinkage direction of the film measured with hot air at 90°C is 2 MPa or more and 10 MPa or less, and the shrinkage stress 30 seconds after the start of measurement is 60% or more and 100% or less of the maximum shrinkage stress.
[0004] Furthermore, a heat-shrinkable polyester film has been proposed in which the amount of amorphous components in the total polyester resin components is strictly controlled, and the hot water heat shrinkage rate at 80°C and 90°C in the longitudinal direction of the film and the hot water heat shrinkage rate at 90°C in the width direction of the film are limited (see Patent Document 2). More specifically, it is a heat-shrinkable polyester film having ethylene terephthalate as its main constituent component and containing one or more monomer components that can become amorphous components in the entire polyester resin component, the total of which is 15 mol % or more. The hot water shrinkage rate of the polyester film in the longitudinal direction of the film is 30% or more at a treatment temperature of 80°C for a treatment time of 10 seconds, and 40% or more at a treatment temperature of 90°C for a treatment time of 10 seconds, and the hot water shrinkage rate in the width direction of the film is 10% or less at a treatment temperature of 90°C for a treatment time of 10 seconds. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2019-081378 A (Claims, etc.) [Patent Document 2] JP 2007-016120 A (Claims, etc.) Summary of the Invention [Problem to be solved by the invention]
[0006] However, in all of the heat-shrinkable films described in Patent Documents 1 and 2, the heat shrinkage rate at a specified temperature and in a specified shrinkage direction is limited to within a specified range, but no consideration has been given to quantitatively controlling the heat shrinkage rate, loss coefficient, etc. In particular, in the case of PET bottles and the like, in which the bottle diameter of the body is not uniform and the horizontal cross-sectional shape of the body is not circular in some parts and has a complex shape, the heat shrinkability is likely to be non-uniform, making it extremely difficult to prevent the occurrence of fine wrinkles.
[0007] Therefore, the inventors of the present invention have discovered that by using a dynamic viscoelasticity measuring device to control the loss coefficients, etc. in multiple temperature regions within respective predetermined ranges when using a polyester-based shrink film derived from a specified polyester-based resin composition on an adherend, it is possible to efficiently and accurately control the heat shrinkage characteristics, wrinkle resistance characteristics, etc., and have completed the present invention. That is, an object of the present invention is to provide a method for using a polyester shrink film having more uniform heat shrinkage properties and excellent wrinkle resistance on an adherend by using a predetermined simplified measurement method. [Means for solving the problem]
[0008] According to the present invention, there is provided a method for using a polyester shrink film derived from a polyester resin composition containing, relative to the total amount (100% by weight), 30 to 80% by weight of an amorphous polyester resin and 20 to 70% by weight of a crystalline polyester resin (excluding low-crystalline polyester resin and crystalline polyester resin having a glass transition temperature of 78°C), comprising the steps of: The amorphous polyester resin is composed of 50 to 80 parts by weight of ethylene glycol, 5 to 20 parts by weight of diethylene glycol, and 20 to 50 parts by weight of 1,4-cyclohexanedimethanol or neopentyl glycol, relative to 100 parts by weight of terephthalic acid per total amount (100 parts by weight) of the reactive components; The crystalline polyester resin is composed of 90 parts by weight or more of terephthalic acid and 90 parts by weight or more of ethylene glycol per 100 parts by weight of the total amount of reactive components. The above-mentioned problems can be solved by providing a method for using a polyester shrink film for an adherend, the method being characterized by satisfying the following requirements (a) to (c). Configuration (a): The loss coefficient measured using a dynamic viscoelasticity measuring device in accordance with JIS K 7244-4 has a first loss coefficient peak in a temperature range of 70°C or higher and 95°C or lower. Configuration (b): In the loss coefficient measured using a dynamic viscoelasticity measuring device in accordance with JIS K 7244-4, the material has a second loss coefficient peak in a temperature range of 110°C or higher and 140°C or lower. Configuration (c): When immersed in 80°C hot water for 10 seconds, the thermal shrinkage rate in the main shrinkage direction is 30% or more. That is, when a polyester-based shrink film derived from a predetermined blend composition is used on an adherend, the loss factor (tan δ) measured using a dynamic viscoelasticity measuring device has peaks (first loss factor peak and second loss factor peak) in multiple temperature ranges, so that the heat shrinkage rate in a wide temperature range can be precisely controlled, and the wrinkle resistance can be improved.
[0009] When configuring a method for using the polyester shrink film of the present invention with an adherend, it is preferable to set the temperature range having the first loss factor peak to a value within the range of 70 to 90°C. By controlling the temperature range having the first loss factor peak in this manner, the difference from the second loss factor peak becomes clearer, making it easier to adjust the heat shrinkage rate over a wide temperature range and to adjust the mechanical properties and durability.
[0010] When configuring the method of using the polyester shrink film of the present invention with respect to an adherend, it is preferable to set the temperature range having the second loss factor peak to a value within the range of 120 to 160°C. By controlling the temperature range having the second loss factor peak in this manner, the difference from the first loss factor peak becomes clearer, making it easier to adjust the heat shrinkage rate over a wide temperature range and to adjust the mechanical properties and durability.
[0011] When configuring a method for using the polyester shrink film of the present invention with an adherend, it is preferable that the height of the second loss factor peak is within a range of 20 to 50 when the height of the first loss factor peak is 100. By controlling the ratio of the height of the first loss factor peak to the height of the second loss factor peak in this manner, it becomes easier to adjust the heat shrinkage rate in a wide temperature range and to adjust the mechanical properties and durability.
[0012] When configuring a method for using the polyester shrink film of the present invention on an adherend, it is preferable that the intrinsic viscosity of the amorphous polyester resin is within a range of 0.6 to 0.85 dL / g, and the intrinsic viscosity of the crystalline polyester resin is within a range of 0.6 to 0.85 dL / g. By controlling the intrinsic viscosity of the amorphous polyester resin and the intrinsic viscosity of the crystalline polyester resin within such ranges, not only is the mixing and dispersing property improved while partial phase separation occurs, but it also becomes easier to adjust the heat shrinkage rate and the mechanical properties and durability.
[0013] In configuring the method of using the polyester shrink film of the present invention on an adherend, it is preferable that the crystalline polyester resin is a homo-PET resin and / or a PCR PET resin. In this way, by controlling the type of crystalline polyester resin, it becomes easy to adjust the heat shrinkage rate, and adjust the mechanical properties and durability, and further, environmental properties can be taken into consideration.
[0014] According to another aspect of the present invention, there is provided a method for using a polyester shrink film derived from a polyester resin composition containing, relative to the total amount (100% by weight), 30 to 80% by weight of an amorphous polyester resin and 20 to 70% by weight of a crystalline polyester resin (excluding low-crystalline polyester resin and crystalline polyester resin having a glass transition temperature of 78°C), comprising the steps of: The amorphous polyester resin is composed of 50 to 80 parts by weight of ethylene glycol, 5 to 20 parts by weight of diethylene glycol, and 20 to 50 parts by weight of 1,4-cyclohexanedimethanol or neopentyl glycol, relative to 100 parts by weight of terephthalic acid per total amount (100 parts by weight) of the reactive components; The crystalline polyester resin is composed of 90 parts by weight or more of terephthalic acid and 90 parts by weight or more of ethylene glycol based on the total amount (100 parts by weight) of the reactive components, The present invention relates to a method for using a polyester shrink film on an adherend, the method being characterized by satisfying the following requirements (a') to (e'). Configuration (a'): In a storage modulus curve obtained using a dynamic viscoelasticity measuring device in accordance with JIS K 7244-4, the first inflection point, at which the storage modulus decreases, is present in a temperature range below 100°C. Configuration (b'): In a storage modulus curve obtained using a dynamic viscoelasticity measuring device in accordance with JIS K 7244-4, there is a second inflection point, at which the storage modulus increases, in a temperature range of 100°C or higher. Configuration (c'): When immersed in 80°C hot water for 10 seconds, the thermal shrinkage rate in the main shrinkage direction is 30% or more. Configuration (d'): In the loss coefficient measured using a dynamic viscoelasticity measuring device in accordance with JIS K 7244-4, the first loss coefficient peak is present in a temperature range of 70°C or higher and 95°C or lower. Configuration: (e´) The difference between the second inflection point temperature and the first loss coefficient peak temperature is 20°C or more. In other words, when a polyester-based shrink film derived from a specified formulation is used on an adherend, the storage modulus curve obtained using a dynamic mechanical analyzer (DMA) has a descending inflection point (first inflection point) where the storage modulus decreases and an inflection point (second inflection point) where the storage modulus increases in different temperature ranges, thereby improving the balance between the glassy region and the rubber elastic region, allowing the thermal shrinkage rate at a specified temperature to be precisely controlled, and ultimately improving the wrinkle resistance.
[0015] According to yet another aspect of the present invention, there is provided a method for using a polyester shrink film derived from a polyester resin composition containing, relative to the total amount (100% by weight), 30 to 80% by weight of an amorphous polyester resin and 20 to 70% by weight of a crystalline polyester resin (excluding low-crystalline polyester resin and crystalline polyester resin having a glass transition temperature of 78°C), comprising the steps of: The amorphous polyester resin is composed of 50 to 80 parts by weight of ethylene glycol, 5 to 20 parts by weight of diethylene glycol, and 20 to 50 parts by weight of 1,4-cyclohexanedimethanol or neopentyl glycol, relative to 100 parts by weight of terephthalic acid per total amount (100 parts by weight) of the reactive components; The crystalline polyester resin is composed of 90 parts by weight or more of terephthalic acid and 90 parts by weight or more of ethylene glycol per 100 parts by weight of the total amount of reactive components. The present invention relates to a method for using a polyester shrink film on an adherend, the method being characterized by satisfying the following requirements (a'') to (c''). Configuration (a´´): In a loss modulus curve obtained using a dynamic viscoelasticity measuring device in accordance with JIS K 7244-4, the first loss modulus peak is present in a temperature range of 70°C or higher and 95°C or lower. Structure (b´´): In a loss modulus curve obtained using a dynamic viscoelasticity measuring device in accordance with JIS K 7244-4, the loss modulus curve has a second loss modulus peak that is convex in the opposite direction to the first loss modulus peak in a temperature range of 110°C or higher and 140°C or lower. Configuration (c´´): When immersed in 80°C hot water for 10 seconds, the thermal shrinkage rate in the main shrinkage direction is 30% or more. In other words, when a polyester-based shrink film derived from a specified formulation is used on an adherend, the loss modulus curve obtained using a dynamic mechanical analyzer (DMA) has a first loss elasticity peak and a second loss elasticity peak in different temperature ranges, thereby improving the balance between the glassy region and the rubber elasticity region, allowing the thermal shrinkage rate at a specified temperature to be precisely controlled, and ultimately improving the wrinkle resistance. [Brief description of the drawings]
[0016] [Figure 1] 1(a) to (c) are diagrams illustrating the configuration of a polyester shrink film. [Diagram 2] 2(a) to (c) are diagrams illustrating the storage modulus curve, loss modulus curve, and loss factor curve of each of the polyester shrink films (Examples 1 to 3) measured using a dynamic viscoelasticity measuring device. [Diagram 3] 3(a) to (c) are diagrams illustrating the storage modulus curve, loss modulus curve, and loss factor curve of the polyester shrink films (Examples 4 to 6) obtained using a dynamic viscoelasticity measuring device. [Figure 4] 4(a) to (c) are diagrams illustrating the storage modulus curves, loss modulus curves, and loss factor curves obtained using a dynamic viscoelasticity measuring device for each of the polyester shrink films (Examples 7 to 8 and Comparative Example 1). [Diagram 5] FIG. 5 is a diagram provided for illustrating the relationship between the blending amount of the amorphous polyester resin / crystalline polyester resin and the temperature of the first peak and the temperature of the second peak of the loss factor curve. [Figure 6] FIG. 6 is a diagram provided for explaining the relationship between the blending amounts of the amorphous polyester resin / crystalline polyester resin and the height of the first peak / height of the second peak of the loss factor curve. [Figure 7] Figure 7 corresponds to Example 1 and is a diagram (photograph) showing the external appearance of a cylindrical label when no wrinkles have occurred, and Figures 7(b) to (d) are enlarged views of areas P, Q, and R of the appearance shown in Figure 7(a), respectively. [Figure 8] Figure 8(a) corresponds to Comparative Example 1 and is a diagram (photograph) showing the appearance of a cylindrical label when wrinkles occur, and Figures 8(b) to (d) are enlarged views of areas S, T, and U of the appearance shown in Figure 8(a), respectively. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] [First embodiment] The first embodiment is a polyester-based shrink film 10 as exemplified in FIG. 1(a) etc., which is a polyester-based shrink film derived from a polyester-based resin composition containing, relative to the total amount (100% by weight), 30 to 90% by weight of amorphous polyester resin and 10 to 70% by weight of crystalline polyester resin, and which satisfies the following configurations (a) to (c). Configuration (a): In accordance with JIS K 7244-4, as shown in Figs. 2 to 4(b), the loss factor measured using a dynamic viscoelasticity measuring device has a first loss factor peak in a temperature range below 100°C. Configuration (b): In accordance with JIS K 7244-4, as shown in Figs. 2(a) to 4(b), the loss factor measured using a dynamic viscoelasticity measuring device has a second loss factor peak in a temperature range of 100°C or higher. Configuration (c): When immersed in 80°C hot water for 10 seconds, the thermal shrinkage rate in the main shrinkage direction is 30% or more. More specifically, the present invention relates to a method for using a polyester shrink film derived from a polyester resin composition containing, relative to the total amount (100 parts by weight), 30 to 80% by weight of an amorphous polyester resin and 20 to 70% by weight of a crystalline polyester resin (excluding low-crystalline polyester resin and crystalline polyester resin having a glass transition temperature of 78°C), wherein the amorphous polyester resin is composed of 50 to 80 parts by weight of ethylene glycol, 5 to 20 parts by weight of diethylene glycol, and 20 to 50 parts by weight of 1,4-cyclohexanedimethanol or neopentyl glycol, relative to 100 parts by weight of terephthalic acid, relative to the total amount (100 parts by weight) of the reactive components, and the crystalline polyester resin is composed of 90 parts by weight or more of terephthalic acid and 90 parts by weight or more of ethylene glycol, relative to the total amount (100 parts by weight) of the reactive components, and the method for using a polyester shrink film on an adherend is characterized in that the following configurations (a) to (c) are satisfied: Configuration (a): The loss coefficient measured using a dynamic viscoelasticity measuring device in accordance with JIS K 7244-4 has a first loss coefficient peak in a temperature range of 70°C or higher and 95°C or lower. Configuration (b): In the loss coefficient measured using a dynamic viscoelasticity measuring device in accordance with JIS K 7244-4, the material has a second loss coefficient peak in a temperature range of 110°C or higher and 140°C or lower. Configuration (c): When immersed in 80°C hot water for 10 seconds, the thermal shrinkage rate in the main shrinkage direction is 30% or more. That is, when a polyester-based shrink film derived from a predetermined blend composition is used on an adherend, the loss factor (tan δ) measured using a dynamic viscoelasticity measuring device has peaks (first loss factor peak and second loss factor peak) in multiple temperature ranges, so that the heat shrinkage rate in a wide temperature range can be precisely controlled, and the wrinkle resistance can be improved. Hereinafter, with reference to the drawings as needed, a method of using the polyester shrink film of the first embodiment with respect to an adherend will be specifically described, dividing it into configurations and the like.
[0018] 1. Polyester resin The polyester resin constituting the polyester-based shrink film of the first embodiment is characterized in that it is derived from a polyester-based resin composition containing 30 to 90% by weight of an amorphous polyester resin and 10 to 70% by weight of a crystalline polyester resin.
[0019] (1) Amorphous polyester resin As the amorphous polyester resin, basically, any polyester resin that is a polymer derived from polyalcohol and dicarboxylic acid and is in an amorphous state at room temperature can be used. Therefore, it is preferable to use an amorphous polyester resin made of a polyalcohol and a hydroxycarboxylic acid, an amorphous polyester resin made of a polyalcohol dicarboxylic acid and a hydroxycarboxylic acid, or a mixture of these polyester resins. Whether or not a resin is an amorphous polyester resin can be determined by the fact that a DSC curve obtained by DSC (differential scanning calorimeter) basically does not show a melting peak of the crystalline portion.
[0020] Here, examples of the polyalcohol that is a raw material component of the amorphous polyester resin include at least one diol such as an aliphatic diol such as ethylene glycol, diethylene glycol, propanediol, butanediol, neopentyl glycol, or hexanediol, an alicyclic diol such as 1,4-hexanedimethanol, or an aromatic diol. Therefore, among these polyalcohols, ethylene glycol, diethylene glycol, and 1,4-hexanedimethanol are particularly preferred. This is because the use of such a polyalcohol makes it easy to react it appropriately with the polyvalent carboxylic acid to obtain a non-crystalline polyester resin whose amorphousness is controlled to a desired state.
[0021] Similarly, examples of dicarboxylic acids as raw material components for polyester resins include at least one of fatty acid dicarboxylic acids such as adipic acid, sebacic acid, and azelaic acid, aromatic dicarboxylic acids such as terephthalic acid, naphthalenedicarboxylic acid, and isophthalic acid, alicyclic dicarboxylic acids such as 1,4-cyclohexanedicarboxylic acid, and ester-forming derivatives thereof. Among these, terephthalic acid is particularly preferred. Similarly, the hydroxycarboxylic acid as a compound component of the polyester resin may be at least one of lactic acid, hydroxybutyric acid, polycaprolactone, and the like.
[0022] Thus, examples of amorphous polyester resins include amorphous polyethylene terephthalate, amorphous polyethylene naphthalate, amorphous polybutylene terephthalate, amorphous polybutylene naphthalate, and amorphous polypropylene terephthalate, and these may be used alone or in combination. In particular, as an example of the amorphous polyester resin, a amorphous polyester resin composed of 50 to 80 parts by weight of ethylene glycol, 5 to 20 parts by weight of diethylene glycol, and 20 to 50 parts by weight of 1,4-cyclohexanedimethanol or neopentyl glycol per 100 parts by weight of terephthalic acid in the total amount (100 parts by weight) of the reaction components can be suitably used. Also, other dicarboxylic acids and diols, or hydroxycarboxylic acids may be used to modify the properties and characteristics of the shrink film, if desired.
[0023] (2) Crystalline polyester resin On the other hand, as the crystalline polyester resin, basically, any polyester resin having a crystalline portion at room temperature can be used. Therefore, polyester resins made of polyalcohol and dicarboxylic acid, polyester resins made of polyalcohol and hydroxycarboxylic acid, polyester resins made of polyalcohol dicarboxylic acid and hydroxycarboxylic acid, or mixtures of these polyester resins are preferred. Whether or not a resin is a crystalline polyester resin can be determined by the fact that a melting peak of the crystalline portion basically appears in a predetermined temperature range in a DSC curve obtained by a DSC (differential scanning calorimeter).
[0024] Here, the polyalcohol, which is a compound component of the polyester resin, may be at least one diol, such as an aliphatic diol such as ethylene glycol, diethylene glycol, propanediol, butanediol, neopentyl glycol, or hexanediol, an alicyclic diol such as 1,4-hexanedimethanol, or an aromatic diol, which are similar to the reactive components of the amorphous polyester resin. Among these, ethylene glycol, diethylene glycol, and 1,4-hexanedimethanol are particularly preferable.
[0025] Similarly, examples of dicarboxylic acids as reactive components of polyester resins include at least one of fatty acid dicarboxylic acids such as adipic acid, sebacic acid, and azelaic acid, aromatic dicarboxylic acids such as terephthalic acid, naphthalenedicarboxylic acid, and isophthalic acid, alicyclic dicarboxylic acids such as 1,4-cyclohexanedicarboxylic acid, and ester-forming derivatives thereof, which are similar to the reactive components of amorphous polyester resins.
[0026] Thus, examples of crystalline polyester resins include polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate, polybutylene naphthalate, and polypropylene terephthalate, and these may be used alone or in combination. In particular, as an example of the crystalline polyester resin, a crystalline polyester resin containing 100 parts by weight of terephthalic acid and 100 parts by weight of ethylene glycol in the total amount of the reaction components can be suitably used. As an example of the crystalline polyester resin, a crystalline polyester resin composed of 90 to 99 parts by weight of terephthalic acid, 90 to 99 parts by weight of ethylene glycol, 0.5 to 5 parts by weight of isopropanol, and 1 to 10 parts by weight of diethylene glycol, relative to the total amount (100 parts by weight) of the reactive components, can be suitably used.
[0027] (3) Mixing ratio The polyester-based shrink film is characterized in that the polyester-based resin composition constituting the polyester-based shrink film contains, relative to the total amount (100% by weight), 20 to 90% by weight of an amorphous polyester resin and 10 to 80% by weight of a crystalline polyester resin. The reason for this is that by limiting the blending amounts of the amorphous polyester resin and the crystalline polyester resin in this manner, they are homogeneously mixed while undergoing partial phase separation, which may make it difficult to adjust the viscoelastic properties such as the loss factor. Therefore, the thermal shrinkage rate and the maximum shrinkage stress near the shrinkage temperature can be more easily adjusted to the desired range, and the haze value and the like can also be easily controlled quantitatively.
[0028] More specifically, if the content of amorphous polyester resin is less than 20% by weight or more than 90% by weight, it becomes difficult to adjust the viscoelastic properties such as the loss coefficient, and it may become difficult to control the thermal shrinkage rate, mechanical strength, or maximum shrinkage stress of the polyester-based shrink film near the shrinkage temperature. Therefore, it is more preferable that the total amount of the polyester resin contains 25 to 85% by weight of amorphous polyester resin and 15 to 75% by weight of crystalline polyester resin, and it is even more preferable that the total amount of the polyester resin contains 30 to 80% by weight of amorphous polyester resin and 20 to 70% by weight of crystalline polyester resin.
[0029] 2.Configuration (a) The configuration (a) is characterized in that, in accordance with JIS K 7244-4 and as shown in Figs. 2 to 4(b), the loss factor (tan δ) obtained using a dynamic viscoelasticity measuring device has a first loss factor peak in a temperature range below 100°C. The reason for this, although related to the later-described configuration (b), is that for a polyester-based shrink film derived from a specified blend composition, the loss coefficient measured using a dynamic viscoelasticity measuring device has a first loss coefficient peak in a specified temperature range, so that the heat shrinkage rate at a specified temperature can be controlled with high precision, and thus the wrinkle resistance can be improved.
[0030] It is more preferable that the temperature region where the first loss factor peak appears is less than 100°C, and usually falls within the range of 80 to less than 98°C. The reason for this is that by controlling the peak temperature of the loss factor obtained in the temperature range below 100°C in the loss factor curve to a value within a predetermined range, it becomes difficult to adjust the viscoelastic properties such as the loss factor, but it may become easy to control the heat shrinkage rate, mechanical strength, maximum shrinkage stress, etc. near the shrinkage temperature of the polyester-based shrink film.
[0031] Here, referring to FIG. 5, the relationship between the blending amount of the amorphous polyester resin / crystalline polyester resin and the temperatures of the first loss factor peak and the second loss factor peak will be described. That is, the horizontal axis of FIG. 5 indicates the blending amount of the amorphous polyester resin / crystalline polyester resin, and the vertical axis indicates the temperatures of the first loss factor peak and the second loss factor peak, respectively. As can be seen from the characteristic curve in FIG. 5, there is a good correlation between the blending amount of the amorphous polyester resin / crystalline polyester resin and the temperature of the first loss factor peak and the temperature of the second loss factor peak. Therefore, although it depends on the types of the amorphous polyester resin and the crystalline polyester resin, it is understood that by controlling the blending amounts of these, the first loss factor peak temperature and the second loss factor peak temperature can be controlled, respectively.
[0032] Moreover, it is more preferable that the height of the first loss factor peak obtained by such loss factor is usually set to a value within the range of 1.5 to 2.5. That is, when the height of the first loss factor peak in the loss factor curve is less than 1.5, the balance of the blending amounts of the amorphous polyester resin and the crystalline polyester resin and the mixing state are deteriorated, making it difficult to adjust the viscoelastic properties such as the loss factor, but it may become easy to control the heat shrinkage rate, mechanical strength, maximum shrinkage stress, etc. around the shrinkage temperature of the polyester shrink film. Therefore, it is more preferable that the height of the first loss factor peak obtained by the loss factor is set to a value within the range of 1.7 to 2.3, and further preferably to a value within the range of 1.8 to 2.0.
[0033] Also, referring to FIG. 6, the relationship between the blending amount of the amorphous polyester resin / crystalline polyester resin and the ratio of the height of the first loss factor peak / the height of the second loss factor peak in the loss factor curve will be described. Here, referring to FIG. 6, the relationship between the blending amount of the amorphous polyester resin / crystalline polyester resin and the temperature of the first peak and the temperature of the second peak of the loss factor curve will be described. That is, the horizontal axis of FIG. 6 indicates the blending amount of the amorphous polyester resin / crystalline polyester resin, and the vertical axis indicates the ratio of the height of the first loss factor peak / the height of the second loss factor peak in the loss factor curve. As can be seen from the characteristic curve in FIG. 6, there is a good correlation between the blending amount of the amorphous polyester resin / crystalline polyester resin and the ratio of the height of the first loss factor peak / the height of the second loss factor peak in the loss factor curve. Therefore, although it depends on the types of the amorphous polyester resin and the crystalline polyester resin, it is understood that by controlling the blending amounts of these, the ratio of the height of the first loss factor peak / the height of the second loss factor peak in the loss factor curve, and further the heights of the individual peaks can be controlled, respectively.
[0034] With respect to the first loss factor peak obtained by dynamic viscoelasticity measurement, it is preferable that the difference between the first loss factor peak temperature and the temperature at which a first inflection point appears, where the storage modulus decreases, in the storage modulus curve, is 5°C or more. The reason for this is that by controlling the first loss factor peak temperature to a value within a predetermined range in consideration of the first inflection point temperature in the storage modulus curve, the blending ratio of the amorphous polyester resin / crystalline polyester resin can be controlled within a predetermined range and in a well-balanced manner. In other words, by taking into consideration the difference between the first loss factor peak temperature and the temperature at which the first inflection point appears in the storage modulus curve, not only is the amorphous polyester resin / crystalline polyester resin mixed and dispersed well while undergoing partial phase separation, but adjustment of the heat shrinkage rate, etc. becomes easier. Therefore, the difference between the first loss factor peak temperature of the loss factor and the first inflection point temperature of the storage modulus is more preferably within the range of 8 to 18°C, and even more preferably within the range of 10 to 15°C.
[0035] 3. Configuration (b) As configuration (b), the loss factor measured using a dynamic viscoelasticity measuring device in accordance with JIS K 7244-4 has a second loss factor peak in a temperature range of 100°C or higher, as shown in Figs. 2 to 4(b). The reason for this, although related to the above-mentioned feature (a), is that for a polyester-based shrink film derived from a specified blend composition, the loss coefficient measured using a dynamic viscoelasticity measuring device has a second loss coefficient peak in a specified temperature range, so that the heat shrinkage rate at a specified temperature can be controlled with high precision, and thus the wrinkle resistance can be improved.
[0036] The temperature range in which the second loss factor peak appears is a temperature range of 100°C or higher, and is usually preferably set to a value within the range of 110 to 150°C, and more preferably to a value within the range of 120 to 130°C. The reason for this is that by controlling the temperature range where the second loss factor peak appears, it becomes easier to adjust the viscoelastic properties such as the loss factor, and this may make it easier to control the thermal shrinkage rate, mechanical strength, maximum shrinkage stress, etc., of the polyester-based shrink film near the shrinkage temperature.
[0037] Generally, it is more preferable that the height of the second loss factor peak is set to a value within the range of 0.2 to 1. That is, when the height of the first loss factor peak in the loss factor curve is a value less than 0.2 or exceeds 1, the balance of the blending amounts of the amorphous polyester resin and the crystalline polyester resin or the mixed state may deteriorate. This makes it difficult to adjust viscoelastic properties such as the loss coefficient, but may make it easier to control the thermal shrinkage rate, mechanical strength, or maximum shrinkage stress of the polyester shrink film near the shrinkage temperature. Therefore, it is more preferable that the height of the first loss factor peak obtained by the loss factor is set to a value within the range of 0.3 to 0.8, and even more preferable that it is set to a value within the range of 0.5 to 0.6.
[0038] It is more preferable to determine the height of the second loss factor peak in consideration of the height of the first loss factor peak. In other words, when the height of the first loss factor peak is taken as 100, the height of the second loss factor peak is preferably set to a value within a range of 20-50. The reason for this is that by controlling the ratio of the height of the first loss factor peak / the height of the second loss factor peak in this way, the balance of the blending amounts of the amorphous polyester resin and the crystalline polyester resin and the mixed state become good, and it becomes easier to adjust the heat shrinkage rate in a wide temperature range and to adjust the mechanical properties and durability. Therefore, when the height of the first loss factor peak is taken as 100, the height of the second loss factor peak is more preferably set to a value within the range of 25 to 45, and further preferably to a value within the range of 20 to 40.
[0039] 4. Composition (c) Configuration (c) is characterized in that the thermal shrinkage rate in the main shrinkage direction (TD) when immersed in 80° C. warm water for 10 seconds is 30% or more. The reason for this is that if the desired heat shrinkage rate can be easily obtained at the commonly used temperature of 80°C under such heat shrinkage temperature conditions, the heat shrinkage rate can be precisely controlled over a wide temperature range, thereby improving the wrinkle resistance. This improves the wrinkle resistance of the polyester shrink film, and also makes it easy to adjust the mechanical properties, heat shrinkage rate, and the like. The heat shrinkage rate in the main shrinkage direction when immersed in 80° C. warm water for 10 seconds is preferably within the range of 35 to 55%, and more preferably within the range of 38 to 50%.
[0040] 5.Configuration (d) As the configuration (d), it is preferable that the storage modulus at 80° C. is set to a value within the range of 40 MPa to 300 MPa in a storage modulus curve obtained by dynamic viscoelasticity measurement. The reason for this is that by controlling the storage modulus in a predetermined temperature range to a specific range, it becomes easier to identify the inflection point (first inflection point) in the storage modulus curve. Therefore, even if there is manufacturing variation, the inflection point of the storage modulus in a specified temperature range can be controlled, and the wrinkle resistance can be further improved in a stable manner. Therefore, in the storage modulus curve, the storage modulus at 80° C. is more preferably set to a value within the range of 50 MPa to 200 MPa, and further preferably to a value within the range of 60 MPa to 150 MPa.
[0041] 6. Configuration (e) As the configuration (e), it is preferable that the absolute value of the difference (IV1-IV2) between the intrinsic viscosity of the amorphous polyester resin (sometimes referred to as IV1) and the intrinsic viscosity of the crystalline polyester resin (sometimes referred to as IV2) is 0.5 or less. In this way, by controlling the absolute value of the difference between the intrinsic viscosity of the amorphous polyester resin and the intrinsic viscosity of the crystalline polyester resin to a value within a predetermined range, the blending ratio of the amorphous polyester resin / crystalline polyester resin can be easily controlled within a predetermined range, making it even easier to adjust the heat shrinkage rate. Moreover, by limiting the difference between these intrinsic viscosities, the mechanical properties and durability can be made more stable. Therefore, it is more preferable that the absolute value of the difference (IV1-IV2) between the intrinsic viscosity (IV1) of the amorphous polyester resin and the intrinsic viscosity (IV2) of the crystalline polyester resin is set to a value within the range of 0.001 to 0.1, and even more preferable that it is set to a value within the range of 0.01 to 0.08.
[0042] The intrinsic viscosity of the amorphous polyester resin is preferably set to a value within the range of 0.6 to 0.85 dL / g. Although it is also related to the intrinsic viscosity of the crystalline polyester resin described later, by setting the intrinsic viscosity of the amorphous polyester resin to a value within a predetermined range in this manner, not only does partial phase separation occur between the amorphous polyester resin and the crystalline polyester resin while improving the mixing and dispersing properties, but it also becomes easy to adjust the heat shrinkage rate over a wide temperature range and to adjust the mechanical properties and durability. Therefore, the intrinsic viscosity of the amorphous polyester resin is more preferably set to a value within the range of 0.65 to 0.83 dL / g, and further preferably set to a value within the range of 0.7 to 0.8 dL / g.
[0043] The intrinsic viscosity of the crystalline polyester resin is preferably set to a value within the range of 0.6 to 0.85 dL / g. Although it is also related to the intrinsic viscosity of the crystalline polyester resin described below, by setting the intrinsic viscosity of the amorphous polyester resin to a value within a predetermined range in this manner, not only does partial phase separation occur between the amorphous polyester resin and the amorphous polyester resin while improving the mixing and dispersing properties, but it also becomes easy to adjust the heat shrinkage rate over a wide temperature range and to adjust the mechanical properties and durability. Therefore, the intrinsic viscosity of the crystalline polyester resin is more preferably set to a value within the range of 0.65 to 0.83 dL / g, and further preferably set to a value within the range of 0.7 to 0.8 dL / g.
[0044] 7.Thickness The thickness of the polyester shrink film is usually preferably within a range of 10 to 200 μm. The reason for this is that by specifically limiting the film thickness before heat shrinkage to a value within a predetermined range in this manner, it becomes easier to manufacture the film with a uniform thickness, and it also becomes easier to control the heat shrinkage rate and the maximum shrinkage stress, making it easier to prevent the occurrence of uneven shrinkage. Therefore, the film thickness before heat shrinkage is more preferably set to a value within the range of 20 to 100 μm, and further preferably to a value within the range of 30 to 50 μm.
[0045] 8. Thermal properties of polyester shrink film (1) Thermal shrinkage rate in the TD direction 1 In a polyester-based shrink film, the main shrinkage direction is the TD direction, and the thermal shrinkage rate (A2) in the TD direction when shrunk at a temperature of 90°C for 10 seconds is a value of 40 to less than 80%. The reason for this is that by limiting the 90° C. heat shrinkage rate to less than 40 to 80%, a good heat shrinkage rate can be obtained in the polyester shrink film during heat shrinking, and therefore the maximum shrinkage stress can also be easily obtained. Therefore, the 90° C. heat shrinkage in the TD direction is more preferably set to a value within the range of 42 to less than 75%, and even more preferably to a value within the range of 45 to 70%.
[0046] (2) Thermal shrinkage in the TD direction 2 For polyester shrink films, this is a constituent requirement that the heat shrinkage rate (A3) in the TD direction when shrunk at a temperature of 70°C for 10 seconds must be less than 25%. The reason for this is that by limiting the 70° C. heat shrinkage rate, a good heat shrinkage rate can be obtained in the polyester shrink film during heat shrinking, and therefore the maximum shrinkage stress can also be easily obtained. Therefore, the 70° C. heat shrinkage in the TD direction is more preferably set to a value within the range of 5 to 23%, and even more preferably to a value within the range of 10 to 20%.
[0047] (3) Thermal shrinkage rate in MD direction 3 In polyester shrink films, the direction perpendicular to the main shrinkage direction is the MD direction, and the constituent requirement is that the thermal shrinkage rate (B1) in the MD direction when shrunk at a temperature of 80°C for 10 seconds is 5% or less. The reason for this is that by limiting the 80°C heat shrinkage rate in the MD direction to a value of 5% or less, a good heat shrinkage rate can be obtained in the main heat shrinkage direction of the polyester-based shrink film during heat shrinking, and ultimately the maximum shrinkage stress can also be easily obtained. Therefore, it is more preferable that the 80° C. heat shrinkage rate in the MD direction is set to a value within the range of 3% or less, and even more preferable that it is set to a value of 1% or less.
[0048] (4) Thermal shrinkage in MD direction 4 In polyester shrink films, the direction perpendicular to the main shrinkage direction is the MD direction, and the constituent requirement is that the thermal shrinkage rate (B2) in the MD direction when shrunk at a temperature of 90°C for 10 seconds is 10% or less. The reason for this is that by limiting the 90°C heat shrinkage rate in the MD direction to a value of 10% or less, a good heat shrinkage rate can be obtained in the polyester-based shrink film during heat shrinking, and ultimately the maximum shrinkage stress can also be easily obtained. Therefore, it is more preferable that the 90° C. heat shrinkage rate in the MD direction is set to a value of 8% or less, and further preferably to a value of 5% or less.
[0049] (5) Stretch ratio in MD The stretch ratio in the MD direction of the polyester shrink film (average MD direction stretch ratio, sometimes simply referred to as MD direction stretch ratio) is preferably set to a value within the range of 100 to 200%. The reason for this is that by specifically limiting the MD stretch ratio to a value within a predetermined range, and also specifically limiting the predetermined heat shrinkage rate and its standard deviation, etc., to values each within a predetermined range, the occurrence of fine wrinkles can be further suppressed. Therefore, the MD stretch ratio is more preferably set to a value within the range of 105 to 180%, and further preferably to a value within the range of 110 to 160%.
[0050] (6) Stretch ratio in TD direction The stretch ratio in the TD direction of the polyester-based shrink film (sometimes referred to as the average TD direction stretch ratio or simply the TD direction stretch ratio) is preferably within the range of 200 to 600%, more preferably within the range of 220 to 550%, and even more preferably within the range of 250 to 500%. The reason for this is that by specifically limiting the TD stretch ratio to a value within a predetermined range, and also specifically limiting the predetermined heat shrinkage rate and its standard deviation, etc., to values each within a predetermined range, the occurrence of fine wrinkles can be further suppressed.
[0051] (7) Haze value It is preferable that the haze value of the polyester shrink film before heat shrinkage, measured in accordance with JIS K 7105, is 5% or less. The reason for this is that by specifically limiting the haze value to a value within a specified range in this manner, the transparency of the polyester-based shrink film can be easily controlled quantitatively, and since the transparency is good, the versatility of the film can be further enhanced. More specifically, if the haze value of the film before heat shrinkage exceeds 5%, the transparency decreases, which may make it difficult to apply the film to decorative applications such as PET bottles. On the other hand, if the haze value of the film before heat shrinkage becomes too small, it becomes difficult to control it stably, and the production yield may decrease significantly. Therefore, in the configuration (g), the haze value of the film before heat shrinkage is more preferably set to a value within the range of 0.1 to 3%, and even more preferably to a value within the range of 0.5 to 1%.
[0052] (8) Composition of polyester shrink film It is preferable to incorporate various additives into the polyester shrink film or to attach them to one or both sides of the film. More specifically, at least one of hydrolysis inhibitors, antistatic agents, ultraviolet absorbers, infrared absorbers, colorants, organic fillers, inorganic fillers, organic fibers, inorganic fibers, etc. is preferably blended in an amount of 0.01 to 10% by weight, more preferably 0.1 to 1% by weight, based on the total weight of the polyester-based shrink film.
[0053] As shown in FIG. 1(b), it is also preferable to laminate other resin layers 10a, 10b containing at least one of these various additives on one or both sides of the polyester shrink film 10. In this case, when the thickness of the polyester shrink film is taken as 100%, the single layer thickness or total thickness of the other resin layers to be additionally laminated is preferably set to a value within the range of 0.1 to 10%.
[0054] The resin as the main component constituting the other resin layer may be a polyester resin similar to that of the polyester-based shrink film, or it is preferable that it is at least one of a different acrylic resin, an olefin resin, a urethane resin, a rubber resin, etc.
[0055] Furthermore, it is also preferable to make the polyester-based shrink film have a multi-layer structure to further prevent hydrolysis and provide mechanical protection, or to provide a shrinkage rate adjustment layer 10c on the surface of the polyester-based shrink film 10 so that the shrinkage rate of the polyester-based shrink film is uniform within the plane, as shown in Figure 1(c). Such a shrinkage adjusting layer can be laminated by using an adhesive, a coating method, a heat treatment, or the like depending on the shrinkage characteristics of the polyester-based shrink film.
[0056] More specifically, the thickness of the shrinkage rate adjustment layer is in the range of 0.1 to 3 μm, and if the shrinkage rate of the polyester-based shrink film at a specified temperature is excessively large, it is preferable to laminate a shrinkage rate adjustment layer of a type that suppresses this. When the shrinkage rate of a polyester shrink film at a given temperature is excessively small, it is preferable to laminate a shrinkage rate adjusting layer that expands the shrinkage rate. Therefore, the present invention aims to obtain a desired shrinkage rate for a polyester-based shrink film by using a shrinkage rate adjusting layer, without producing various types of shrink films with different shrinkage rates.
[0057] [Second embodiment] The second embodiment is a polyester-based shrink film 10 as exemplified in Figure 1(a) etc., which is a polyester-based shrink film derived from a polyester-based resin composition containing 30 to 90 weight % of amorphous polyester resin and 10 to 70 weight % of crystalline polyester resin relative to the total amount (100 weight %), and is a method for using the polyester-based shrink film on an adherend satisfying the following configurations (a') to (c'). Configuration (a'): In accordance with JIS K 7244-4, as shown in Figs. 2 to 4(b), the storage modulus curve obtained using a dynamic viscoelasticity measuring device has a descending inflection point in a temperature range below 100°C. Configuration (b'): In accordance with JIS K 7244-4, as shown in Figs. 2 to 4(b), the storage modulus curve obtained using a dynamic viscoelasticity measuring device has an upward inflection point in a temperature range of 100°C or higher. Configuration (c'): When immersed in 80°C hot water for 10 seconds, the thermal shrinkage rate in the main shrinkage direction is 30% or more. More specifically, the present invention relates to a method for using a polyester shrink film derived from a polyester resin composition containing, relative to the total amount (100 parts by weight), 30 to 80% by weight of an amorphous polyester resin and 20 to 70% by weight of a crystalline polyester resin (excluding low-crystalline polyester resins and crystalline polyester resins having a glass transition temperature of 78°C), the amorphous polyester resin is composed of 50 to 80 parts by weight of ethylene glycol, 5 to 20 parts by weight of diethylene glycol, and 20 to 50 parts by weight of 1,4-cyclohexanedimethanol or neopentyl glycol, relative to 100 parts by weight of terephthalic acid per 100 parts by weight of the total amount (100 parts by weight) of the reaction components, and the crystalline polyester resin is composed of 90 parts by weight or more of terephthalic acid and 90 parts by weight or more of ethylene glycol, relative to the total amount (100 parts by weight) of the reaction components, The present invention relates to a method for using a polyester shrink film on an adherend, the method being characterized by satisfying the following requirements (a') to (e'). Configuration (a'): In a storage modulus curve obtained using a dynamic viscoelasticity measuring device in accordance with JIS K 7244-4, the first inflection point, at which the storage modulus decreases, is present in a temperature range below 100°C. Configuration (b'): In a storage modulus curve obtained using a dynamic viscoelasticity measuring device in accordance with JIS K 7244-4, there is a second inflection point, at which the storage modulus increases, in a temperature range of 100°C or higher. Configuration (c'): When immersed in 80°C hot water for 10 seconds, the thermal shrinkage rate in the main shrinkage direction is 30% or more. Configuration (d'): In the loss coefficient measured using a dynamic viscoelasticity measuring device in accordance with JIS K 7244-4, the first loss coefficient peak is present in a temperature range of 70°C or higher and 95°C or lower. Configuration: (e´) The difference between the second inflection point temperature and the first loss coefficient peak temperature is 20°C or more. In other words, for a polyester-based shrink film derived from a specified blend composition, by having a first inflection point (descending inflection point) and a second inflection point (ascending inflection point) in different temperature ranges in a storage modulus curve obtained using a dynamic mechanical analyzer (DMA), a good balance is achieved between the glassy region and the rubber elastic region, allowing the thermal shrinkage rate at a specified temperature to be precisely controlled, and ultimately improving wrinkle resistance. The types and amounts of the amorphous polyester resin and crystalline polyester resin used in the second embodiment, as well as other factors such as the thermal shrinkage rate and the structure of the shrink film, can be similar to those in the first embodiment.
[0058] [Third embodiment] The third embodiment is a polyester-based shrink film 10 as exemplified in Figure 1(a) etc., which is a polyester-based shrink film derived from a polyester-based resin composition containing 30 to 90 weight % of amorphous polyester resin and 10 to 70 weight % of crystalline polyester resin relative to the total amount (100 weight %), and which satisfies the following configurations (a'') to (c''). Configuration (a´´): In accordance with JIS K 7244-4, as shown in Figs. 2 to 4(b), a loss modulus curve obtained using a dynamic viscoelasticity measuring device has a first loss coefficient peak in a temperature range below 100°C. Configuration (b´´): In accordance with JIS K 7244-4, as shown in Figs. 2 to 4(b), a loss modulus curve obtained using a dynamic viscoelasticity measuring device has a second inverse peak that is convex in the opposite direction to the first loss factor peak in a temperature range of 100°C or higher. Configuration (c´´): When immersed in 80°C hot water for 10 seconds, the thermal shrinkage rate in the main shrinkage direction is 30% or more. More specifically, the present invention relates to a method for using a polyester shrink film derived from a polyester resin composition containing, relative to the total amount (100% by weight), 30 to 80% by weight of an amorphous polyester resin and 20 to 70% by weight of a crystalline polyester resin (excluding low-crystalline polyester resin and crystalline polyester resin having a glass transition temperature of 78°C), comprising the steps of: The amorphous polyester resin is composed of 50 to 80 parts by weight of ethylene glycol, 5 to 20 parts by weight of diethylene glycol, and 20 to 50 parts by weight of 1,4-cyclohexanedimethanol or neopentyl glycol, relative to 100 parts by weight of terephthalic acid per total amount (100 parts by weight) of the reactive components; The crystalline polyester resin is composed of 90 parts by weight or more of terephthalic acid and 90 parts by weight or more of ethylene glycol per 100 parts by weight of the total amount of reactive components. The present invention relates to a method for using a polyester shrink film on an adherend, the method being characterized by satisfying the following requirements (a'') to (c''). Configuration (a´´): In a loss modulus curve obtained using a dynamic viscoelasticity measuring device in accordance with JIS K 7244-4, the first loss modulus peak is present in a temperature range of 70°C or higher and 95°C or lower. Structure (b´´): In a loss modulus curve obtained using a dynamic viscoelasticity measuring device in accordance with JIS K 7244-4, the loss modulus curve has a second loss modulus peak that is convex in the opposite direction to the first loss modulus peak in a temperature range of 110°C or higher and 140°C or lower. Configuration (c´´): When immersed in 80°C hot water for 10 seconds, the thermal shrinkage rate in the main shrinkage direction is 30% or more. In other words, for a polyester-based shrink film derived from a specified blend composition, a loss modulus curve obtained using a dynamic mechanical analyzer (DMA) has a first loss factor peak and a second loss factor peak in different temperature ranges, respectively, which improves the balance between the glassy region and the rubber elastic region, making it possible to precisely control the heat shrinkage rate at a specified temperature and ultimately improve wrinkle resistance. The types and amounts of the amorphous polyester resin and crystalline polyester resin used in the third embodiment, as well as other factors such as the thermal shrinkage rate and the structure of the shrink film, can be similar to those in the first embodiment.
[0059] [Fourth embodiment] The fourth embodiment is an embodiment relating to a method of using the polyester shrink film according to any one of the first to third embodiments. In other words, any known method for using shrink films can be suitably applied. For example, when implementing the method for using a polyester shrink film, first, the polyester shrink film is cut to an appropriate length and width, and formed into a long cylindrical object. Next, the long cylindrical object is fed to an automatic label attachment device (shrink labeler), further cut to the required length, and further fitted onto the outside of a PET bottle or the like filled with the contents.
[0060] Next, the polyester shrink film fitted around the PET bottle or the like is subjected to a heat treatment by passing through a hot air tunnel or steam tunnel at a predetermined temperature. These tunnels provide radiant heat such as infrared rays, or heated steam at about 90°C is sprayed onto the polyester shrink film from the surrounding area, uniformly heating the film and causing it to shrink. Therefore, when the standard deviation of the thermal shrinkage rate in the TD direction is 20% or less, it is possible to quickly obtain a labeled container by adhering it to the outer surface of a PET bottle or the like, as shown in Figures 7(a) to (d). On the other hand, when the standard deviation of the thermal shrinkage rate in the TD direction exceeds 20%, as shown in Figures 8(a) to (d), there are areas from the top to the bottom of the bottle body where the label cannot conform to the shape of the bottle periphery, and wrinkles are also clearly observed.
[0061] [Fifth embodiment] The fifth embodiment relates to a method for producing a polyester shrink film for use in the application of the polyester shrink films of the first to third embodiments to an adherend. That is, typically, it is preferable to produce a predetermined polyester shrink film according to the following steps.
[0062] 1. Preparation and mixing of raw materials First, it is preferable to prepare, as raw materials, base materials and additives such as crystalline polyester resin, non-crystalline polyester resin, rubber-based resin, antistatic agent, hydrolysis inhibitor, etc. Next, the prepared crystalline polyester resin, non-crystalline polyester resin, etc. are preferably charged into the stirring vessel while being weighed, and mixed and stirred using a stirring device until the mixture becomes uniform.
[0063] 2. Preparation of the base sheet Next, the homogeneously mixed raw materials are preferably dried to an absolutely dry state. Next, typically, extrusion molding is preferably carried out to prepare a raw sheet having a predetermined thickness. More specifically, for example, extrusion molding can be performed using an extruder (manufactured by Tanabe Plastic Machinery Co., Ltd.) with an L / D of 24 and an extrusion screw diameter of 50 mm under conditions of an extrusion temperature of 260°C, to obtain a raw sheet of a predetermined thickness (usually 10 to 100 μm).
[0064] 3. Making polyester shrink film Next, the obtained raw sheet is heated and pressed while being moved over or between rolls using a shrink film manufacturing device to produce a polyester-based shrink film. In other words, it is preferable to crystallize the polyester molecules that make up the polyester-based shrink film into a predetermined shape by stretching the film in a predetermined direction while heating and pressing it at a predetermined stretching temperature and stretching ratio, while basically expanding the film width. Then, in this state, by heat fixing at a predetermined temperature, it is possible to produce the heat-shrinkable polyester shrink film used for decorations, labels, and the like according to the first to third embodiments.
[0065] 4. Evaluation process using a dynamic viscoelasticity measuring device Typically, when producing the polyester shrink films of the first to third embodiments, it is preferable to include an evaluation step using a dynamic mechanical analyzer (DMA) according to the following procedure. That is, it is preferable to prepare a specified polyester shrink film as a measurement object, and measure and evaluate viscoelastic properties such as the storage modulus curve, loss modulus curve, and loss factor (Tan δ) in a specified temperature range using a dynamic viscoelasticity measuring device in accordance with JIS K7244-4. In this case, it is preferable to confirm in advance that the thickness of the polyester shrink film is within a predetermined range.
[0066] 5.Other The obtained polyester shrink film is immersed in hot water maintained at a specified temperature and for a specified time using a specified heating device, or is heat-treated to cause the polyester shrink film to thermally shrink, and the thermal shrinkage rate is measured. It is also preferable to measure the haze, glass transition point, and various thermal properties of the polyester shrink film in advance. It is also preferable to attach the obtained polyester shrink film to an adherend such as a PET bottle, heat treat it in that state under predetermined conditions, and evaluate the uniformity of shrinkage of the polyester shrink film.
[0067] In addition, it is preferable to provide a predetermined inspection process in which the following characteristics are measured continuously or intermittently for the produced polyester shrink film. In other words, by using such a specified inspection process to measure the following characteristics and confirm that they fall within the specified ranges, a polyester-based shrink film with more uniform shrinkage characteristics can be produced. 1) Visual inspection of the appearance of polyester shrink film 2) Thickness variation measurement 3) Haze measurement 4) Measurement of glass transition temperature 5) Measurement of melting point and heat of fusion 6) Tensile modulus measurement 7) Tear strength measurement 8) SS curve measurement EXAMPLES
[0068] The present invention will be described in detail below based on examples. However, the scope of the present invention will not be narrowed by the description of the examples without a particular reason. The polyester resins used in Example 1 and the like are as follows.
[0069] (PETG1) Amorphous polyester resin consisting of dicarboxylic acid: 100 parts by weight of terephthalic acid, diol: 63 parts by weight of ethylene glycol, 24 parts by weight of 1,4-cyclohexanedimethanol, and 13 parts by weight of diethylene glycol (glass transition point: 69.5°C, intrinsic viscosity: 0.78 dL / g)
[0070] (PETG2) Amorphous polyester resin consisting of dicarboxylic acid: 100 parts by weight of terephthalic acid, diol: 59.9 parts by weight of ethylene glycol, 12.4 parts by weight of 1,4-cyclohexanedimethanol, and 12.4 parts by weight of diethylene glycol (glass transition point: 75°C, intrinsic viscosity: 0.78 dL / g)
[0071] (PETG3) Dicarboxylic acid: 100 parts by weight of terephthalic acid, diol: 70 parts by weight of ethylene glycol, 28.2 parts by weight of neopentyl glycol, 12.4 parts by weight of diethylene glycol. Amorphous polyester resin (glass transition point: 76.5°C, intrinsic viscosity: 0.75 dL / g)
[0072] (APET1) Dicarboxylic acid: 100 mol% terephthalic acid, diol: 100 mol% ethylene glycol, crystalline polyester resin (glass transition point: none, intrinsic viscosity: 0.65 dL / g)
[0073] (APET2) Dicarboxylic acid: 100 mol% terephthalic acid, diol: 100 mol% ethylene glycol, crystalline polyester resin (glass transition point: none, intrinsic viscosity: 0.71 dL / g)
[0074] (PCR1) Dicarboxylic acid: 98.6 parts by weight of terephthalic acid, 1.4 parts by weight of isophthalic acid, diol: 97.3 parts by weight of ethylene glycol, 2.7 parts by weight of diethylene glycol Recycled crystalline polyester resin (glass transition point: none, intrinsic viscosity: 0.72 dL / g)
[0075] (PCR2) Dicarboxylic acid: 98.6 parts by weight of terephthalic acid, 1.4 parts by weight of isophthalic acid, diol: 97.3 parts by weight of ethylene glycol, 2.7 parts by weight of diethylene glycol Recycled crystalline polyester resin (glass transition point: none, intrinsic viscosity: 0.82 dL / g)
[0076] [Example 1] 1. Preparation of polyester shrink film In a stirring vessel, 70 parts by weight of a non-crystalline polyester resin (PETG1) and 30 parts by weight of a crystalline polyester resin (APET1) were placed and uniformly mixed and stirred to prepare raw materials. Next, this raw material was dried and then extrusion molded at an extrusion temperature of 260° C. using an extruder with an L / D of 24 and an extrusion screw diameter of 50 mm (manufactured by Tanabe Plastic Machinery Co., Ltd.) to obtain a raw sheet having a thickness of 100 μm.
[0077] Next, using a shrink film manufacturing device, a 30 μm thick polyester shrink film was produced from the original sheet at a preheating temperature of 75°C, a stretching temperature of 75°C, a stretching ratio (MD direction: 100%, TD direction: 500%), and a heat setting temperature of 60°C.
[0078] 2. Evaluation of polyester shrink film (1) Evaluation 1: Thickness variation The thickness of the obtained polyester shrink film (reference value was 30 μm, which was the desired value) was measured using a micrometer (n=6), and evaluated according to the following criteria. The results are shown in Table 1. ⊚: The average thickness variation is within the range of the reference value ±0.1 μm. ◯: The average thickness variation is within the range of the reference value ±0.5 μm. Δ: The average thickness variation is within the range of the reference value ±1.0 μm. ×: The average thickness variation is within the range of the reference value ±3.0 μm.
[0079] (2) Evaluation 2: Thermal shrinkage rate in the TD direction 1 The obtained polyester shrink film was immersed in hot water at 80° C. for 10 seconds in a thermostatic bath to cause thermal shrinkage. Next, the heat shrinkage rate (A1) was calculated from the dimensional change before and after the heat treatment at a specified temperature (80°C hot water) according to the following formula, and evaluated according to the following criteria. The obtained results are shown in Table 1. Heat shrinkage rate = (film length before heat shrinkage - film length after heat shrinkage) / film length before heat shrinkage x 100 ⊚: The heat shrinkage rate (A1) is within the range of 40 to 50%. ◯: The heat shrinkage rate (A1) is within the range of 30 to 60%, and is outside the range of ⊚. △: The heat shrinkage rate (A1) is a value within the range of 20 to 70%, and is outside the above range of ◯. ×: The heat shrinkage rate (A1) is less than 20% or more than 70%.
[0080] (3) Evaluation 3: Thermal shrinkage rate in the TD direction 2 The obtained polyester shrink film was immersed in hot water at 90° C. for 10 seconds in a thermostatic bath to cause thermal shrinkage. Next, the heat shrinkage rate (A2) was calculated from the dimensional change before and after the heat treatment at a specified temperature (90°C hot water) according to the following formula, and evaluated according to the following criteria. The obtained results are shown in Table 1. Heat shrinkage rate = (film length before heat shrinkage - film length after heat shrinkage) / film length before heat shrinkage x 100 ⊚: The heat shrinkage rate (A2) is within the range of 45 to 70%. ◯: The heat shrinkage rate (A2) is within the range of 40 to 80%, and is outside the range of ⊚. △: The heat shrinkage rate (A2) is within the range of 35 to 90%, and is outside the above range of ◯. ×: The heat shrinkage rate (A2) is less than 35% or more than 90%.
[0081] (4) Rating 4: Intrinsic viscosity 0.5 g of each polyester resin raw material used in the examples was dissolved in 50 ml of a mixed solvent of phenol / 1,1,2,2-tetrachloroethane (weight ratio: 60 / 40). Next, the temperature of the mixed solvent was set to 30° C., and the intrinsic viscosity (η) was measured using an Ostwald viscometer. The results are shown in Table 1. Next, the absolute value of the difference (IV1-IV2) between the intrinsic viscosity (IV1) of the amorphous polyester resin used and the intrinsic viscosity (IV2) of the crystalline polyester resin used was calculated, and evaluated according to the following criteria. The obtained results are shown in Table 1. ◎: The difference in absolute value is 0.05 or less. ◯: The difference in absolute value is 0.08 or less, which is outside the range of ⊚ above. △: The difference in absolute value is 0.1 or less, and is outside the above range of ◯. ×: The difference in absolute value exceeds 0.1.
[0082] (5) Rating 5: Wrinkle resistance A cylindrical PET bottle (volume: 500 ml) filled with commercially available drinking water was prepared. Next, a polyester shrink film was slit to a width of 26 cm to obtain a long shrink film, and 1 mm-wide perforations were made along the longitudinal direction of the film, and 1,3-dioxolane was applied to the ends in the width direction. Next, the ends in the width direction were overlapped and glued together so that the overlap was about 1 cm, to obtain a cylindrical label with a diameter of about 8 cm. Further, this cylindrical label was cut in the longitudinal direction at 16 cm intervals to obtain a plurality of cylindrical labels. Next, the tubular label was placed over the body of the prepared cylindrical PET bottle, and the bottle was placed on a conveyor belt through a steam tunnel maintained at 85°C and moved at a speed of 6 m / min, causing the tubular label to thermally shrink so that it adhered closely to the body of the cylindrical PET bottle from the top to the bottom. Next, the tubular label after heat shrinkage was visually observed, and wrinkle resistance was evaluated based on whether wrinkles of a specified length (1 cm or more) or width (1 mm or more) occurred according to the following criteria. The results are shown in Table 1. ⊚: No wrinkles were observed in any of the five cylindrical labels. ◯: No wrinkles were observed in three or more of the five cylindrical labels. △: No wrinkles were observed in one or more of the five cylindrical labels. ×: The occurrence of predetermined wrinkles was observed in all of the five cylindrical labels.
[0083] (6) Evaluation 6: Storage modulus The obtained polyester shrink film was cut into a 15 mm wide x 0.05 mm thick (cross-sectional area 0.75 mm 2 ) and the sample length (distance between the grippers) was 15 mm, and the cut specimen was prepared as a test piece. Next, the viscoelastic properties of the prepared test pieces were measured using a dynamic viscoelasticity measuring device (TA Instruments, DMA Q800) in accordance with JIS K7244-4. More specifically, during the measurement, an appropriate static stress (1.4 MPa) was applied by an automatic tension mechanism, and the specimen was kept at -30°C for a while using liquid nitrogen as a cooling medium. After that, the material was heated at a temperature increase rate of 3°C / min and a sine wave with a displacement amplitude of 15 μm and a frequency of 1 Hz was applied to measure the storage modulus E' and loss modulus E'' as shown in Figure 2(a), and the loss factor (tan δ) was also calculated. In this case, the upper limit temperature was set to 150° C., but the measurement was terminated when the set static stress could no longer be maintained due to the elongation of the sample. The storage moduli obtained at 50° C., 70° C. and 80° C. are shown in Table 2. Furthermore, the temperatures of the first inflection point and the second inflection point were calculated from the obtained storage modulus curve, and are shown in Table 2.
[0084] (7) Rating 7: Loss modulus The loss moduli at 50° C., 70° C. and 80° C. obtained by the dynamic viscoelasticity measurement are shown in Table 2. From the obtained loss modulus curve, the temperature of the first loss modulus peak and the temperature of the second loss modulus peak were calculated and are shown in Table 2.
[0085] (8) Rating 8: Loss factor From the storage modulus curve obtained by the dynamic viscoelasticity measurement, the first loss factor peak temperature of the loss factor (tan δ) was calculated and evaluated according to the following criteria. The obtained results are shown in Table 2. ⊚: The first loss coefficient peak temperature is within the range of 78 to 90°C. ◯: The first loss coefficient peak temperature is a value within the range of 75 to 93° C. and is a value other than the above-mentioned ⊚. △: The first loss coefficient peak temperature is a value within the range of 70 to 95° C., and is a value other than the above ◯. ×: The first loss coefficient peak temperature is less than 70°C or more than 95°C.
[0086] Similarly, the second loss factor peak temperature of the loss factor (tan δ) was calculated from the storage modulus curve obtained by the dynamic viscoelasticity measurement, and evaluated according to the following criteria. The results are shown in Table 2. ⊚: The second loss coefficient peak temperature is within the range of 120 to 130°C. ◯: The second loss coefficient peak temperature is a value within the range of 115 to 135° C. and is a value other than the above-mentioned ⊚. △: The second loss coefficient peak temperature is a value within the range of 110 to 140° C. and is a value other than the above ◯. ×: The second loss coefficient peak temperature is less than 110°C or more than 140°C.
[0087] (9) Rating 9: Temperature difference between the second inflection point and the first loss factor peak From the second inflection point and the first loss factor peak obtained in the dynamic viscoelasticity measurement, the difference between the temperature of the second inflection point and the temperature of the first loss factor peak was calculated, and the evaluation was performed according to the following criteria. The obtained results are shown in Table 2. ⊚: The difference between the second inflection point temperature and the first loss coefficient peak temperature is 40°C or more. ◯: The difference between the second inflection point temperature and the first loss coefficient peak temperature is 20° C. or more, and is outside the range of the above-mentioned ⊚. △: The difference between the second inflection point temperature and the first loss coefficient peak temperature is 10° C. or more, and is outside the above range of ◯. ×: The difference between the second inflection point temperature and the first loss coefficient peak temperature is less than 10°C.
[0088] [Examples 2 to 8] In Examples 2 to 8, various polyester shrink films were prepared in the same manner as in Example 1, except that the types of resins used were changed as shown in Table 1. The thickness variation, heat shrinkage rates (A1, A2), storage modulus, etc. were evaluated in the same manner as in Example 1. The results are shown in Tables 1 and 2.
[0089] That is, in Example 2, 30 parts by weight of non-crystalline polyester resin (PETG1) and 70 parts by weight of crystalline polyester resin (APET1) were mixed and used as a raw material, and a polyester-based shrink film was produced by changing the extrusion conditions, and the viscoelastic properties and the like were evaluated as shown in Fig. 2(b) in the same manner as in Example 1. The results are shown in Tables 1 and 2.
[0090] In Example 3, instead of the crystalline polyester resin (APET1), crystalline polyester resin (APET2) was mixed at a ratio of 30 parts by weight, which was used as a raw material, and a polyester-based shrink film was produced under different extrusion conditions in the same manner as in Example 1. As shown in Fig. 2(c), the viscoelastic properties and the like were evaluated. The results are shown in Tables 1 and 2.
[0091] In Example 4, instead of the crystalline polyester resin (APET1), the crystalline polyester resin (APET2) was used, 30 parts by weight of the non-crystalline polyester resin (PETG1) and 70 parts by weight of the crystalline polyester resin (APET2) were mixed as the raw material, and the extrusion conditions were changed to produce a polyester-based shrink film. Except for this, the same procedure as in Example 1 was followed, and the viscoelastic properties, etc. were evaluated as shown in Figure 3(a). The obtained results are shown in Tables 1 and 2.
[0092] In Example 5, instead of the crystalline polyester resin (APET1), recycled crystalline polyester resin (PCR1) was mixed at a ratio of 30 parts by weight, which was used as a raw material, and a polyester-based shrink film was produced by changing the extrusion conditions. The same procedures as in Example 1 were followed, and the viscoelastic properties, etc. were evaluated as shown in Figure 3(b). The obtained results are shown in Tables 1 and 2.
[0093] In Example 6, instead of the crystalline polyester resin (APET1), recycled crystalline polyester resin (PCR1) was used, and 30 parts by weight of non-crystalline polyester resin (PETG1) and 70 parts by weight of recycled crystalline polyester resin (PCR1) were mixed as raw materials, and a polyester-based shrink film was produced by changing the extrusion conditions in the same manner as in Example 1. As shown in Figure 3(c), the viscoelastic properties, etc. were evaluated. The obtained results are shown in Tables 1 and 2.
[0094] In Example 7, instead of the crystalline polyester resin (APET1), recycled crystalline polyester resin (PCR2) was mixed at a ratio of 30 parts by weight, which was used as a raw material, and a polyester-based shrink film was produced under different extrusion conditions in the same manner as in Example 1. As shown in Fig. 4(a), the viscoelastic properties and the like were evaluated. The obtained results are shown in Tables 1 and 2.
[0095] In Example 8, 30 parts by weight of non-crystalline polyester resin (PETG1) and 70 parts by weight of recycled crystalline polyester resin (PCR2) were mixed instead of crystalline polyester resin (APET1), and polyester shrink film was produced by changing extrusion conditions in the same manner as in Example 1. As shown in Fig. 4(b), viscoelastic properties were evaluated. The obtained results are shown in Tables 1 and 2.
[0096] [Comparative Example 1] In Comparative Example 1, various polyester-based shrink films were produced in the same manner as in Example 1, except that the type of amorphous polyester resin was changed as shown in Table 1. The thickness variation, thermal shrinkage rate (A1, A2), and dynamic viscoelasticity measurements were evaluated in the same manner as in Example 1.
[0097] That is, in Comparative Example 1, crystalline polyester resin was not used, and 100 parts by weight of non-crystalline polyester resin (PETG1) was used as a raw material, and the extrusion conditions were changed to produce a polyester-based shrink film, but the same procedures were followed as in Example 1, and the viscoelastic properties, etc. were evaluated as shown in Figure 4(c). The obtained results are shown in Tables 1 and 2.
[0098] [Table 1]
[0099] [Table 2]
[0100] [Examples 9 to 10] In Examples 9 and 10, polyester-based shrink films were prepared and evaluated in the same manner as in Example 1, except that the amorphous polyester was changed from PETG1 to PETG2 and PETG3, respectively. As a result, it was confirmed that almost the same results as those in Example 1 were obtained in terms of the thickness variation, the thermal shrinkage rates (A1, A2), and the dynamic viscoelasticity measurements.
[0101] [Comparative Examples 2 to 3] In Comparative Examples 2 and 3, polyester-based shrink films were prepared and evaluated in the same manner as in Example 1, except that the amorphous polyester was changed from PETG1 to PETG2 and PETG3, respectively. As a result, it was confirmed that in Comparative Examples 2 and 3, the results of the thickness variation, the heat shrinkage rates (A1, A2), and the dynamic viscoelasticity measurements were almost the same as those in Comparative Example 1. [Industrial Applicability]
[0102] According to the present invention, in a polyester shrink film derived from a specified polyester resin composition, the loss coefficient and other properties are measured at multiple temperature ranges using a dynamic viscoelasticity measuring device, and by controlling each within a specified range, it is possible to efficiently and accurately control the heat shrinkage characteristics, wrinkle resistance characteristics, and other properties. Therefore, the polyester shrink film of the present invention can be applied to various PET bottles, etc., significantly expanding its versatility and thus having extremely high industrial applicability.
Claims
1. A method for using a polyester-based shrink film derived from a polyester-based resin composition containing, relative to the total amount (100% by weight), 30 to 80% by weight of an amorphous polyester resin and 20 to 70% by weight of a crystalline polyester resin (excluding low-crystalline polyester resin and crystalline polyester resin having a glass transition temperature of 78°C), comprising the steps of: The amorphous polyester resin is composed of 50 to 80 parts by weight of ethylene glycol, 5 to 20 parts by weight of diethylene glycol, and 20 to 50 parts by weight of 1,4-cyclohexanedimethanol or neopentyl glycol, relative to 100 parts by weight of terephthalic acid per total amount (100 parts by weight) of the reactive components; The crystalline polyester resin comprises 90 parts by weight or more of terephthalic acid and 90 parts by weight or more of ethylene glycol per 100 parts by weight of the total amount of reactive components, A method for using a polyester shrink film on an adherend, the method comprising the steps of: Configuration (a): In the loss factor measured using a dynamic viscoelasticity measuring device in accordance with JIS K 7244-4, the first loss factor peak is present in a temperature range of 70°C or higher and 95°C or lower. Configuration (b): In the loss factor measured using a dynamic viscoelasticity measuring device in accordance with JIS K 7244-4, the material has a second loss factor peak in a temperature range of 110°C or higher and 140°C or lower. Configuration (c): The thermal shrinkage rate in the main shrinkage direction when immersed in warm water at 80° C. for 10 seconds is 30% or more.
2. 2. The method for using the polyester shrink film according to claim 1, wherein the temperature range below 100°C having the first loss factor peak is set to a value within the range of 70 to 90°C.
3. 3. The method for using the polyester shrink film according to claim 1 or 2, wherein the temperature range of 100°C or higher having the second loss factor peak is set to a value within the range of 120 to 160°C.
4. 3. The method for using the polyester-based shrink film according to claim 1 or 2, characterized in that the height of the second loss factor peak is set to a value within a range of 20 to 50 when the height of the first loss factor peak is set to 100.
5. 3. A method for using the polyester-based shrink film according to claim 1 or 2, characterized in that the intrinsic viscosity of the amorphous polyester resin is set to a value within the range of 0.6 to 0.85 dL / g, and the intrinsic viscosity of the crystalline polyester resin is set to a value within the range of 0.6 to 0.85 dL / g.
6. 3. The method for using the polyester shrink film according to claim 1 or 2, wherein the crystalline polyester resin is a homo-PET resin and / or a PCR PET resin.
7. A method for using a polyester-based shrink film derived from a polyester-based resin composition containing, relative to the total amount (100% by weight), 30 to 80% by weight of an amorphous polyester resin and 20 to 70% by weight of a crystalline polyester resin (excluding low-crystalline polyester resin and crystalline polyester resin having a glass transition temperature of 78°C), comprising the steps of: The amorphous polyester resin is composed of 50 to 80 parts by weight of ethylene glycol, 5 to 20 parts by weight of diethylene glycol, and 20 to 50 parts by weight of 1,4-cyclohexanedimethanol or neopentyl glycol, relative to 100 parts by weight of terephthalic acid per total amount (100 parts by weight) of the reactive components; The crystalline polyester resin comprises 90 parts by weight or more of terephthalic acid and 90 parts by weight or more of ethylene glycol based on the total amount (100 parts by weight) of the reactive components; A method for using a polyester shrink film on an adherend, the method comprising the steps of: Configuration (a'): In a storage modulus curve obtained using a dynamic viscoelasticity measuring device in accordance with JIS K 7244-4, the first inflection point, at which the storage modulus decreases, is present in a temperature range below 100°C. Configuration (b'): In a storage modulus curve obtained using a dynamic viscoelasticity measuring device in accordance with JIS K 7244-4, there is a second inflection point, at which the storage modulus increases, in a temperature range of 100°C or higher. Configuration (c'): The thermal shrinkage rate in the main shrinkage direction when immersed in warm water at 80°C for 10 seconds is 30% or more. Configuration (d'): In the loss coefficient measured using a dynamic viscoelasticity measuring device in accordance with JIS K 7244-4, the first loss coefficient peak is present in a temperature range of 70°C or higher and 95°C or lower. Configuration: (e') The difference between the second inflection point temperature and the first loss factor peak temperature is 20°C or more.
8. A method for using a polyester-based shrink film derived from a polyester-based resin composition containing, relative to the total amount (100% by weight), 30 to 80% by weight of an amorphous polyester resin and 20 to 70% by weight of a crystalline polyester resin (excluding low-crystalline polyester resin and crystalline polyester resin having a glass transition temperature of 78°C), comprising the steps of: The amorphous polyester resin comprises, with respect to 100 parts by weight of terephthalic acid in the total amount (100 parts by weight) of the reaction components, 50 to 80 parts by weight of ethylene glycol, 5 to 20 parts by weight of diethylene glycol, and 20 to 50 parts by weight of 1,4-cyclohexanedimethanol or neopentyl glycol; The crystalline polyester resin comprises 90 parts by weight or more of terephthalic acid and 90 parts by weight or more of ethylene glycol per 100 parts by weight of the total amount of reactive components, A method for using a polyester shrink film on an adherend, the method comprising the steps of: Configuration (a″): In a loss modulus curve obtained using a dynamic viscoelasticity measuring device in accordance with JIS K 7244-4, the first loss modulus peak is present in a temperature range of 70° C. or higher and 95° C. or lower. Configuration (b″): In a loss modulus curve obtained using a dynamic viscoelasticity measuring device in accordance with JIS K 7244-4, a second loss modulus peak that is convex in the opposite direction to the first loss modulus peak is present in a temperature range of 110° C. or higher and 140° C. or lower. Configuration (c″): The thermal shrinkage rate in the main shrinkage direction when immersed in warm water at 80° C. for 10 seconds is 30% or more.
Citation Information
Patent Citations
Labeled container and method for manufacturing labeled container
JP2022074157A
Polyester shrink film
JP6837188B1
Polyester-based heat shrink film
WO2023032429A1
Heat-shrinkable polyester film and label, and method for production thereof
JP2007016120A
Heat-shrinkable polyester film and packaging
JP2019081378A